Hubungan Self-Control dengan Nomophobia pada Mahasiswa Program Sarjana Keperawatan di Kota Makassar - Perang, Blasius; Yasinta Patrisia Gertrudis (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Nomophobia is an anxiety or dependence on a person when far apart from a smartphone. Dependence on this smartphone causes a lack of social interaction from other people.  One of internal factors that can affect the level of nomophobia. Self-control is the ability to regulate behavior that can have a positive impact, especially in using of a smartphone. The aim of this study was to explore   the relationship between self-control with nomophobia in city of Makassar. This type of research in a non-experimental, observational analytic study with a cross sectional study approach. The population in the study was the nurse students in city of Makassar and applied a probability sampling with a proportional stratified random sampling approach with a total sample of 184 respondents. The instrument used was a questionnaire consisting self-control of 30 statements and nomophobia of 20 statements.  The statistical test applied a non-parametric chi square test with a significance value α=0,05. The result of the study where the value of ρ=0,001,   The result showed that there was   a relationship between self-control with nomophobia in nursing students in city of Makassar. This research is   expected so that students can control themselves in using smartphones so that they do not always depend on gadget and further improve communication with fellow students